Prediction of Newhall navel orange internal quality based on digital microscopy - Gao, Shumin; Cao, Cong; Hu, Dingyi; Xu, Rangwei; Cheng, Yunjiang; Zhu, Ming; Li, Shanjun (International Journal of Agricultural and Biological Engineering, 2021)
The traditional technology for internal quality detection of citrus fruit is believed to be destructive, inefficient, and error-prone. To address these issues, a novel method has been developed to evaluate nondestructively the sugar-acid ratio (SAR) of soluble solids by using the oil glands density (OGD). In this study, a total of 584 samples with different widths were collected. The sample data were correlated that the SAR and OGD decreased with time during storage. The relevance with time was significant between SAR and OGD of citrus positively correlated in the calibration group (R2=0.82), which indicated that OGD could be used to predict the internal quality of citrus. It indicated that a new generation of digital microscopy could provide an alternative to predict nondestructively the internal quality of citrus fruit, as well as some theoretical insight for further studies of online quality detection in the future. Keywords: citrus, nondestructive, oil glands, internal quality, storage, microscopy DOI: 10.25165/j.ijabe.20211406.5996 Citation: Gao S M, Cao C, Hu D Y, Xu R W, Cheng Y J, Chen H, et al. Prediction of Newhall navel orange internal quality based on digital microscopy. Int J Agric & Biol Eng, 2021; 14(6): 222–227.